Diabetic Dermopathy and Poor Glycemic Control among Diabetic Patients in Sulaimaniyah, Kurdistan, Iraq - Ali Mozan Dhahir Elethawi (Advanced Medical Journal)
Background and objectives: Diabetes mellitus is the commonest endocrine disorder among the general population. Shin spots or diabetic dermopathy is the foremost common cutaneous sign of diabetes mellitus. Sporadic shin spots may occur in non-diabetic people. However, 4 or more spots are highly specific of microangiopathy in diabetics and may indicate a poor glycaemic control.  This study was done to evaluate prevalence of diabetic dermopathy among a group of Iraqi diabetic patients living in Sulaimaniyah, region of Kurdistan and its correlation with the state of diabetic control.